2009
DOI: 10.1063/1.3231614
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the magnetoelectric response of Metglas/polyvinylidene fluoride laminates by exploiting the flux concentration effect

Abstract: Magnetic flux concentration effect of Metglas as a function of its sheet aspect ratio was investigated for Metglas/polyvinylidene fluoride laminates. Taking advantage of this effect, the magnetoelectric voltage coefficient of 21.46 V/cm∙Oe for a laminate with 1 mm wide and 30 mm long Metglas sheet (25 μm thick) is achieved, which is much higher than those reported earlier in similar laminates without making use of the flux concentration effect. The results demonstrate an effective means to significantly enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
80
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 19 publications
3
80
0
Order By: Relevance
“…In particular, the nanofocus diffraction studies show that the MS strain changes induced in the PE component can indeed be enhanced in such structures, as suggested by previous more macroscopic ME measurements. 2,26,27 The initial strain and also the field induced changes in the ZnO are localized near the Metglas/ZnO interface, with the latter being well correlated with the magnetization behavior observed by MOKE microscopy. The possibility to determine in single ME microcomposites both the magnetization and strain changes in the 10 À5 range with micron spatial resolution, as demonstrated in this work, is crucial for understanding these complex systems and will also be highly useful for studies of other similar functional microsystems.…”
supporting
confidence: 55%
“…In particular, the nanofocus diffraction studies show that the MS strain changes induced in the PE component can indeed be enhanced in such structures, as suggested by previous more macroscopic ME measurements. 2,26,27 The initial strain and also the field induced changes in the ZnO are localized near the Metglas/ZnO interface, with the latter being well correlated with the magnetization behavior observed by MOKE microscopy. The possibility to determine in single ME microcomposites both the magnetization and strain changes in the 10 À5 range with micron spatial resolution, as demonstrated in this work, is crucial for understanding these complex systems and will also be highly useful for studies of other similar functional microsystems.…”
supporting
confidence: 55%
“…For adjusting the self-biased ME response, it was found that high magnetic flux concentration in the magnetic phase has positive effect. 11,14 By considering the influence of demagnetization effect, the effective magnetic flux density can be expressed as 11…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] For obtaining a more sensitive magnetic sensor, the magnetostrictive phase in the laminate composite is recommended to have higher effective relative permeability µ r and lower saturation magnetization µ 0 M s . 7,8 But unfortunately, most of the magnetostrictive materials have low µ r . 9,10 Recently, the ME composites with Metglas have highest sensitivity and lowest noise for ME sensors.…”
mentioning
confidence: 99%